Direct Gold Plating Selectively on UV Modified Polymer Film Using Tiopronin-Gold. Issue 6 (1st January 2015) - Endo, Hitoshi; Tashiro, Katsuhiko; Ma, Hengyi; Mizuhashi, Shoei; Yamamoto, Taibo; Kimizuka, Ryoichi; Takai, Osamu; Honma, Hideo; Cordonier, Christopher E. J.
Abstract : An economic and low toxicity gold plating process for bio-compatible device fabrication was investigated. A tiopronin-gold complex altered by mercaptothiodiazole or mercaptotriazole derivatives gave a form of the complex that could be reduced autocatalytically to enable electroless gold plating. Catalytic ca. 5 nm gold particles were selectively grafted into cycloolefin polymer and polyethylenenaphthalate film surfaces by adsorption of tiopronin-gold complex from solution into 20–30 nm deep ultra-violet light modified surface layers followed by reduction with sodium borohydride. Exposure of the catalyst adsorbed surfaces to baths composed of tiopronin-gold complex, mercaptothiodiazole and ascorbic acid resulted in selective electroless plating on the modified surfaces. Observation of the interface cross-section by transmission electron microscopy revealed that the gold deposits were physically anchored to the substrate by nanometer scale octopus trap like structures.